Moodle x Google Classroom: um estudo comparativo sobre a experiência dos alunos da UFAM/ICET - Maia, Priscila Ribeiro (Brasil, 2021)
This work presents a comparison and evaluation of the user experience (User Experience-UX) between two educational environments, Moodle Mobile Web Service and Google Classroom (in Portuguese Google Classroom). To develop the field study of a qualitative nature, an online questionnaire was applied to students from the Federal University of Amazonas-UFAM/ICET, from the Software Engineering and Information Systems courses, where the aim of this study was to assess the interaction of students with the computational environment, therefore, we saw their perspectives in relation to these systems. The results showed significant differences, in which it was observed that the first system has few usability problems related to difficulties in using some of its features.